Transmisi Budaya Berorientasi Kato Nan Ampek Dalam Pengembangan Karakter Generasi Muda Minang Kabau - Fitri, Maulida; F, Firman; Sukma, Dina (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Education is the primary means for cultural transmission between generations. Through the education process, values, norms and local wisdom are passed on from one generation to the next. This research focuses on the role of education in cultural transfer, especially in the context of student character building. Teachers as the main actors in the education process have a great responsibility in instilling cultural values to students. One example of cultural values that can be taught is the Kato nan Ampek proverb in Minangkabau culture. This proverb teaches good communication ethics, but unfortunately there are still many students who have not applied these values in their daily lives. This study aims to analyze the extent to which education is successful in transferring cultural values, especially ethical values, to students. By understanding the factors that influence the success of the cultural transfer process, it is hoped that a more effective learning strategy can be developed in shaping students' noble character. This research was conducted using the literature study method. The results showed that student character development can be done through the Kato Nan Ampek proverb in a way, the first is a behavioral example, where teaching kato nan ampek to students can be through